Casein kinase 1[Delta] activity: a key element in the Zebrafish circadian timing system - Smadja-Storz, Sima; Foulkes, Nicholas S. (PLOS ONE, 2013)
Zebrafish have become a popular model for studies of the circadian timing mechanism. Taking advantage of its rapid development of a functional circadian clock and the availability of light-entrainable clock-containing cell lines, much knowledge has been gained about the circadian clock system in this species. However, the post-translational modifications of clock proteins, and in particular the phosphorylation of PER proteins by Casein kinase I delta and epsilon (CK1δ and CK1ε), have so far not been examined in the zebrafish. Using pharmacological inhibitors for CK1δ and CK1ε, a pan-CK1δ/ε inhibitor PF-670462, and a CK1ε -selective inhibitor PF-4800567, we show that CK1δ activity is crucial for the functioning of the circadian timing mechanism of zebrafish, while CK1ε plays a minor role. The CK1δ/ε inhibitor disrupted circadian rhythms of promoter activity in the circadian clock-containing zebrafish cell line, PAC-2, while the CK1ε inhibitor had no effect. Zebrafish larvae that were exposed to the CK1δ/ε inhibitor showed no rhythms of locomotor activity while the CK1ε inhibitor had only a minor effect on locomotor activity. Moreover, the addition of the CK1δ/ε inhibitor disrupted rhythms of aanat2 mRNA expression in the pineal gland. The pineal gland is considered to act as a central clock organ in fish, delivering a rhythmic hormonal signal, melatonin, which is regulated by AANAT2 enzymatic activity. Therefore, CK1δ plays a key role in the circadian timing system of the zebrafish. Furthermore, the effect of CK1δ inhibition on rhythmic locomotor activity may reflect its effect on the function of the central clock in the pineal gland as well as its regulation of peripheral clocks.
Im Titel ist Delta als griechischer Buchstabe dargestellt
Gesehen am 19.07.2017